The peoples eccho to the Parliaments declarations, concerning a personall treaty with the King. Containing a collection of some few passages out of severall declarations and expresses of the Lords and Commons assembled in Parliament at Westminster, concerning a personall treaty with the King. Together with a humble enforcement of the equity and justice of the said expresses; humbly presented, not only to the review of the Honourable Parliament: but also to the serious consideration of the Lord Major, aldermen, and commons of London in Comon-Counsell assembled. [electronic resource] :
Summary goes here